Pemanfaatan Refugia dengan Metode â€œBorder Plantâ€ Untuk Mengendalikan Hama Lalat Buah pada Tanaman Pare - Sarni Sarni; Helda Sabban (Jurnal Pertanian Khairun, 2022)
Fruit flies belong to pests that inflict huge losses on farmers, especially fruit and vegetable growers. Damage caused by this fruit fly causes the fruit to become rotten, several ways have been done to inflict fruit flies in Indonesia, but the use of pesticides is still dominant. other efforts are needed, namely by implementing Integrated Pest Management. One of them is ecosystem manipulation by planting using the "border plant" technique or edge plants surrounding the plant with refugia. The use of this technique aims to get natural enemies and polynators to go to the edge plants to forage and breed. The purpose of the study was to determine the influence of refugia planting with "border plant" treatment in suppressing the intensity of fruit fly pest attacks on bitter gourd plants. The study was conducted with a Randomized Group Design (RAK) where there were 5 treatments (controls, kenikir flowers, paper, marigolds, purslane) and 5 repeats. The results showed that all refugia plants gave good results in suppressing fruit fly pest attacks on bitter gourd indicated by the percentage of attack rate only below 10%, the development of pupae and imago populations produced also showed that the average form was relatively very small, namely below 10 per head.Keywords : Border Plant, Fruit Fly, Bitter Gourd Plant